Dinamika Isu Laut Tiongkok Selatan: Analisis Sumber-Sumber Kebijakan Luar Negeri Tiongkok dalam Sengketa - Darmawan, Arief Bakhtiar (Parahyangan Center for International Studies, 2018)
This article aims to observeÂ the behaviour of Chinaâs foreign policy in the conflict of South China Sea (SCS), by analyzing the internal factors and external factors that affect Chinaâs foreign policy. China is one of the parties that take direct claim onÂ the SCS. Chinaâs claim is overlapping with other parties such as Vietnam, Filipina, Malaysia, dan Brunei. InÂ defendingÂ its claims, China seeks to dominate both in the dispute area and in multilateral negotiations. In the dispute area, China seized the area, building land reclamation,Â and attacked other countriesâ shipsÂ under various pretexts. In multilateral negotiations, China rejects the intervention of greatÂ power countries outside the region and maintains ambiguous and non-binding code of conduct.Â China also continues to increase its military power to press other countries. The author arguesÂ that the internal factorsÂ has greater influence on Chinese foreign policy decision and action in the SCSÂ dispute than the external factors. Thus, it could triggers China to keep dominating the issue of SCSÂ disputes.